Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/stem.2574
|View full text |Cite
|
Sign up to set email alerts
|

Murine Rankl−/− Mesenchymal Stromal Cells Display an Osteogenic Differentiation Defect Improved by a RANKL-Expressing Lentiviral Vector

Abstract: Autosomal recessive osteopetrosis (ARO) is a severe bone disease characterized by increased bone density due to impairment in osteoclast resorptive function or differentiation. Hematopoietic stem cell transplantation is the only available treatment; however, this therapy is not effective in RANKL-dependent ARO, since in bone this gene is mainly expressed by cells of mesenchymal origin. Of note, whether lack of RANKL production might cause a defect also in the bone marrow (BM) stromal compartment, possibly cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 62 publications
4
26
0
Order By: Relevance
“…We already reported evidence showing that a similar cell‐scaffold construct was well tolerated and osteoinductive in immunodeficient mice . Here, we verified the in vivo biocompatibility of the cell‐seeded MgHA/Col scaffold and the effect of lentivirally mediated RANKL production in the Rankl −/− mouse.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…We already reported evidence showing that a similar cell‐scaffold construct was well tolerated and osteoinductive in immunodeficient mice . Here, we verified the in vivo biocompatibility of the cell‐seeded MgHA/Col scaffold and the effect of lentivirally mediated RANKL production in the Rankl −/− mouse.…”
Section: Resultssupporting
confidence: 74%
“…Rankl −/− MSCs were transduced with either LVhsRL or mock lentiviral vector at 20 MOI, as previously described, and maintained in MSC complete Mesencult medium (Stemcell Technologies, Vancouver, BC) .…”
Section: Methodsmentioning
confidence: 99%
“…In line with these observations, our group has found that BM-MSCs derived from RANKL-deficient mice display a partial osteogenic differentiation defect, which is improved by restoring the production of the soluble form of the cytokine. Our data suggest that RANKL might contribute to direct MSCs fate in an autocrine/paracrine manner, likely through the interaction with either its receptor RANK (Schena et al, 2017) or the recently identified RANKL receptor LGR4 (Luo et al, 2016) (an R-spondin receptor, suggested to regulate bone formation in synergy with Wnt3a), which are both expressed in MSCs (Schena et al, 2017). On this basis, we might speculate that fine tuning, rather than completely blocking, RANKL could be relevant to regulate bone physiology.…”
Section: Microenvironment Factors Orchestrate Mscs Fatementioning
confidence: 75%
“…MSCs, identified in bone tissue as precursor cells of osteoblasts\osteocytes, chondrocytes, and marrow adipocytes, are defined as multipotent cells that can be easily isolated from the stromal fraction. MSCs exhibit in vitro plastic adherence, fibroblast spindle-like shaped morphology, and expression of a panel of surface molecules that is continuously refined to identify unique markers for bona fide MSCs definition (Bourin et al, 2013; Schena et al, 2017). MSCs possess self-renewal and clonogenic capacity and highly proliferate and differentiate at least toward the osteogenic, adipogenic, and chondrogenic lineages both in vitro , by means of specific differentiation media, and in vivo in an ectopic bone formation assay (Schena et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation